2009
DOI: 10.1097/pcc.0b013e318198b096
|View full text |Cite
|
Sign up to set email alerts
|

A novel use of etomidate for intentional adrenal suppression to control severe hypercortisolemia in childhood*

Abstract: The adrenal suppression caused by etomidate, so controversial in the care of the critically ill at present, can be therapeutically used for short-term control of severe hypercortisolemia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Because of these peculiar pharmacokinetic properties, etomidate can be particularly useful in patients with acute and/or lifethreatening complications of CS, such as serious psychosis and severe hypertension (549 -553). Generally, patients with such a severe disease have an ectopic source of CS, but patients with CD treated with etomidate have also been reported (549,(552)(553)(554)(555)(556). Etomidate has been shown to rapidly normalize cortisol levels in almost all patients with CD (549, 552-556).…”
Section: Etomidatementioning
confidence: 99%
See 1 more Smart Citation
“…Because of these peculiar pharmacokinetic properties, etomidate can be particularly useful in patients with acute and/or lifethreatening complications of CS, such as serious psychosis and severe hypertension (549 -553). Generally, patients with such a severe disease have an ectopic source of CS, but patients with CD treated with etomidate have also been reported (549,(552)(553)(554)(555)(556). Etomidate has been shown to rapidly normalize cortisol levels in almost all patients with CD (549, 552-556).…”
Section: Etomidatementioning
confidence: 99%
“…Pivonello Schulte et al (555) demonstrated that an iv infusion of etomidate at dosages between 0.01 and 0.1 mg/kg/h might be sufficient to inhibit adrenal steroidogenesis within a wide margin of safety. In several subsequent studies, etomidate has been administered as iv infusion at dosages ranging from 0.02 to 0.08 mg/kg/h, occasionally preceded by an etomidate bolus of 0.03 mg/kg (549,552,553,556). Preda et al (549) have recommended low-dose etomidate iv infusion rates of 0.04 -0.05 mg/kg/h, with a dose titration dependent on circulating cortisol levels when a partial blockade is required; indeed, in specific cases, the dosage of etomidate might be 0.5-1 mg/h, when a complete blockade is required; in this latter case, iv hydrocortisone is required to prevent or treat adrenal insufficiency induced by the block of etomidate ("block and replace").…”
Section: Etomidatementioning
confidence: 99%
“…There are acute clinical situations, such as the association of severe hypercortisolaemia with complications such as respiratory failure or acute psychosis, where rapid control of cortisol secretion is necessary in order to allow emergency therapy such as bilateral adrenalectomy. Intravenous etomidate infusions administered in an intensive care environmentat doses ranging from 1 to 3.5 mg/h have been documented to be effective in suppressing hypercortisolaemia in three paediatric CD patients [ 44 , 46 , 91 ].…”
Section: Treatment Of Paediatric Cushing’s Diseasementioning
confidence: 99%
“…Etomidate, a commonly used short-acting intravenous anesthetic, is a potent inhibitor of side chain cleavage enzyme 11-b-hydroxylase, aldosterone synthase, as well as an inhibitor of 17-a-hydroxylase [27,120,124,137]. There have been a number of case reports on the successful use of etomidate in controlling hypercortisolemia in seriously ill patients with CD even in the pediatric population [123,138]. Etomidate's use is limited by the need to be given intravenously.…”
Section: Steroidogenesis Inhibitorsmentioning
confidence: 99%